2017
DOI: 10.6001/zemesukiomokslai.v24i1.3441
|View full text |Cite
|
Sign up to set email alerts
|

The effect of biological preparation Fertenat on spring wheat productivity and quality

Abstract: The research of the biological preparation Fertenat effect on spring wheat was investigated at the Experimental Station of Aleksandras Stulginskis University in Calc(ar)i-Epihypogleyic Luvisol (LVG-pw-cc) during 2013–2014. Spring wheat was grown according to the requirements of the National Agricultural Products Quality System. Biological preparation Fertenat had a significant effect on the elements of spring wheat yield structure and the values of chemical composition parameters, influenced by the rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Bulgari et al (2015) suggest that bio-preparations (amino acids) improve the growth of agricultural crops and their resistance to adverse environmental factors, improve plant photosynthetic intensity, resistance to bacteria, fungi and viruses and enhance crop productivity. The effects of biopreparations on the productivity of various agricultural crops under Lithuania's climate conditions have been more comprehensively studied by Jakienė (2013), Jakienė and Spruogis (2015) and Pekarskas et al (2017). Research has shown that the use of bio-preparations reduced the incidence and development of microscopic fungi (Sinkevičienė et al, 2015).…”
mentioning
confidence: 99%
“…Bulgari et al (2015) suggest that bio-preparations (amino acids) improve the growth of agricultural crops and their resistance to adverse environmental factors, improve plant photosynthetic intensity, resistance to bacteria, fungi and viruses and enhance crop productivity. The effects of biopreparations on the productivity of various agricultural crops under Lithuania's climate conditions have been more comprehensively studied by Jakienė (2013), Jakienė and Spruogis (2015) and Pekarskas et al (2017). Research has shown that the use of bio-preparations reduced the incidence and development of microscopic fungi (Sinkevičienė et al, 2015).…”
mentioning
confidence: 99%